Timing of Maternal Depression and Sex‐Specific Child Growth, the Upstate KIDS Study. Issue 1 (1st November 2017) - Park, Hyojun; Sundaram, Rajeshwari; Gilman, Stephen E.; Bell, Griffith; Louis, Germaine M. Buck; Yeung, Edwina H.
Abstract : Objective: Equivocal findings have been reported on the association between maternal depression and children's growth, possibly because of the limited attention to its disproportionate impact by child sex. The relationship between the timing of maternal depression and children's growth was assessed in a population‐based prospective birth cohort, with particular attention to sex differences. Methods: The Upstate KIDS Study comprised 4, 394 children followed through 3 years of age from 2008 to 2010. Maternal depression was measured antenatally by linkage with hospital discharge records before delivery and postnatally by depressive symptoms reported from questionnaires. Children's growth was measured by sex‐ and age‐specific weight, height, weight for height, and BMI. Adjusted linear mixed effects models were used to estimate growth outcomes for the full sample and separately by plurality and sex. Results: Antenatal depression was associated with lower weight for age (−0.24 z score units; 95% confidence interval [CI]: −0.43, −0.05) and height for age (−0.26 z score units; 95% CI: −0.51, −0.02) among singleton boys. Postnatal depressive symptoms were associated with higher weight for height (0.21 z score units; 95% CI: 0.01, 0.42) among singleton girls. Conclusions: The findings of this study suggest that antenatal depression was associated with lower weight and smaller height only for boys, whereas postnatal depressive symptoms were associated with higher weight for height only for girls. The timing of depression and the mechanisms of sex‐specific responses require further examination.